Ответ(ы) на вопрос:
[latex](4+\sqrt{15})^x+(4-\sqrt{15})^x=62[/latex]
замена
[latex](4+\sqrt{15})^x=t[/latex]
тогда [latex](4-\sqrt{15})^x=(\frac{(4-\sqrt{15})(4+\sqrt{15})}{4+\sqrt{15}})^x=[/latex]
[latex]=(\frac{4^2-(\sqrt{15})^2}{4+\sqrt{15}})^x[/latex]
[latex]=(\frac{16-15}{4+\sqrt{15}})^x=\frac{1}{(4+\sqrt{15})^x}=\frac{1}{t}[/latex]
получаем уравнение
[latex]t+\frac{1}{t}=62[/latex]
[latex]t^2-62t+1=0[/latex]
[latex]D=(-62)^2-4*1*1=3840=16^2*15[/latex]
[latex]t_1=\frac{62+16\sqrt{5}}{2*1}=31+8\sqrt{15}[/latex]
[latex]t_2=31-8\sqrt{15}[/latex]
------
возвращаемся к замене
[latex](4+\sqrt{15})^x=31+8\sqrt{15}=(4+\sqrt{15})^2[/latex]
[latex]x_1=2[/latex]
--------
[latex](4+\sqrt{15})^x=31-8\sqrt{15}=(4-\sqrt{15})^2=(4+\sqrt{15})^{-2}[/latex]
[latex]x_2=-2[/latex]
ответ: -2; 2
Не нашли ответ?
Похожие вопросы